Penguatan Daya Saing UMKM Rengginang Desa Tetebatu Melalui Inovasi Branding dan Digital Marketing - Huldiya Syamsiar; Pina Ania Putri; Septina Ziadatin; Nisa Martiana; Rinda Oktavia Suriana; Nila Juliana; Sahrul Jayadi; Eli Mazlin; Ah Agil Alfian; Ely Suliastri; Pera Adriana; Muhammad Riyandi (Universitas Hamzanwadi, 2025)
Rengginang micro, small, and medium enterprises (MSMEs) in Tetebatu Village, Sikur District, East Lombok, have significant potential for development but face challenges in brand management and the utilization of digital technology for marketing. This community service program aimed to strengthen the competitiveness of MSME actors through branding innovation and digital marketing. The activities were conducted in three stages: training on packaging design and brand identity, mentoring in creating digital promotional content, and implementing social media–based marketing strategies. A participatory approach was applied by involving 15 MSME actors from three hamlets: Lingkung Leuk, Lingkung Tengak, and Kembang Sri Leuk. Quantitative results based on pre-test and post-test evaluations showed significant improvements in competencies: the first group increased from 40% to 70%, the second group from 60% to 85%, and the third group from 45% to 80%. On average, branding knowledge improved by 25 percentage points, and social media marketing skills increased proportionally. Furthermore, 80% of participants successfully produced new packaging designs that met modern market standards, and 73% began marketing their products through digital platforms within two weeks after the training. These findings indicate that practice-based collaborative training integrating branding innovation and digital marketing is effective in strengthening MSME capacity to compete in broader markets. In the future, similar programs are recommended to expand to other villages and include business financial management to support sustainability.